Kepemimpinan Perempuan dalam Pengembangan Lembaga Pendidikan di Pondok Pesantren - Wahyuni, Sri Intan; Dwi Lestari, Mega Cahya Dwi Lestari; Sartika, Diana Sartika; Sulasmi, Sulasmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract Indonesia, which has the largest Muslim population in the world, is half female. The Constitution of the Republic of Indonesia provides equal space for men and women in education. However, the principle of gender equality in Islam is sometimes ignored, and unfair treatment is legitimised by interpretations of religious texts. In fact, leadership in Islam does not distinguish between men and women; however, in the pesantren environment, female leaders are still considered taboo by the local community. The symbol of gender segregation in pesantren is manifested in the strict segregation between male and female santri. Male dormitories are often placed more prominently, while female dormitories are often placed at the back and closed. The leadership of pesantren is generally male, which affects the management of education and the division of roles in it. Women are considered to have a role in the domestic sphere and do not have the same role as men in the public sphere. In addition, the leadership of pesantren tends to be passed down from generation to generation to sons, excluding daughters even though they have the same abilities. Female caregivers in pesantren are only considered as successors, while the power over leaders in pesantren is traditionally only owned by boys. These difficulties hinder women's leadership potential in the pesantren environment, resulting in a gap in the provision of rights and opportunities between men and women in the religious context.AbstrakIndonesia, yang memiliki populasi Muslim terbesar di dunia, separuhnya adalah perempuan. Undang-Undang Dasar Negara Republik Indonesia memberikan ruang yang sama antara laki-laki dan perempuan dalam dunia pendidikan. Namun, prinsip kesetaraan gender dalam Islam terkadang diabaikan, dan perlakuan tidak adil dilegitimasi oleh penafsiran teks agama. Faktanya, kepemimpinan dalam IslamÂ tidak membedakan antara laki-laki dan perempuan; Namun di lingkungan pesantren, pemimpin perempuan masih dianggap tabu oleh masyarakat setempat. Simbol segregasi gender di pesantren diwujudkan dalam segregasi yang tegas antara santri laki-laki dan santri perempuan. Asrama laki-laki seringkali ditempatkan lebih menonjol, sedangkan asrama perempuan sering ditempatkanÂ di bagian belakang dan tertutup. Kepemimpinan pesantren pada umumnya adalah laki-laki, hal ini mempengaruhi pengelolaan pendidikan dan pembagian peran di dalamnya. Perempuan dianggap mempunyai peran di ranah domestik dan tidak mempunyai peran yang sama dengan laki-laki di ranah publik. Selain itu, kepemimpinan pesantren cenderung diwariskan dari generasi ke generasi kepada anak laki-laki, tidak termasuk anak perempuan meskipun mereka memiliki kemampuan yang sama. Pengasuh perempuan di pesantren hanya dianggap sebagai penerus, sedangkan kekuasaan atas pemimpin di pesantren secara tradisional hanya dimiliki oleh anak laki-laki. Kesulitan-kesulitan tersebut menghambat potensi kepemimpinan perempuan di lingkungan pesantren sehingga menimbulkan kesenjangan dalam pemberian hak dan kesempatan antara laki-laki dan perempuan dalam konteks agama..